2017
DOI: 10.22608/apo.2016206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corneal Endothelial Cell Loss After Uncomplicated Phacoemulsification Cataract Surgery With Intracameral Phenylephrine

Abstract: Intracameral phenylephrine was not associated with increased risk of postoperative endothelial cell loss or morphological changes. It can be safely injected into the anterior chamber for pupil dilatation before phacoemulsification cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…(25,26) Preservatives such as benzalkonium chloride, chlorobutanol and methylparabens should be avoided. (27,28) Epinephrine containing a bisulfite concentration of 1:16,000 was found to be safe to the corneal endothelium. ( 29) Mydrane® (Théa Pharmaceuticals, Keele, UK), a combination of tropicamide, phenylephrine and lidocaine, is available commercially in Europe.…”
Section: Dilationmentioning
confidence: 99%
“…(25,26) Preservatives such as benzalkonium chloride, chlorobutanol and methylparabens should be avoided. (27,28) Epinephrine containing a bisulfite concentration of 1:16,000 was found to be safe to the corneal endothelium. ( 29) Mydrane® (Théa Pharmaceuticals, Keele, UK), a combination of tropicamide, phenylephrine and lidocaine, is available commercially in Europe.…”
Section: Dilationmentioning
confidence: 99%
“…Although phacoemulsification is a safe procedure, the risk of endothelial cell loss is inherent due to the intraocular maneuvers involved. [13][14][15][16][17][18] In this study, surgical outcomes in surgeries performed by a group of 10 ophthalmology residents at the University of Campinas (UNICAMP) over the course of 18 months of phacoemulsification training (July 2016 to January 2018) were compared. We retrospectively analyzed intraoperative complications, as well as pre-, intra-, and postoperative parameters, in order to compare outcomes among residents of different training levels.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, it has been shown that endothelial cells naturally decrease with age. 6 , 7 In addition, eye surgeries, especially intraocular surgeries, such as cataract surgery, 8 , 9 posterior chamber phakic IOL implantation, 10 , 11 or iris-fixated IOL (iris claw lens), 12 , 13 can reduce the density of these cells. Preoperative endothelial cell density (ECD) examination provides a good predictor of corneal condition after phakic IOL surgery.…”
Section: Introductionmentioning
confidence: 99%